Critical Analysis of the Results of the CPA Exam for the Second Decade of This Century: Empirical Evidence From Puerto Rico - Lozada, Aida R.; Maldonado, Edwin R.; Castro, Segundo (Journal of Applied Business and Economics, 2022)
The research for the first time examines the performance of candidates for the uniform Certified Public Accountant exam in the Hispanic jurisdiction of Puerto Rico from 2010 to 2019. The study presents an innovative method of classifying the quality of accounting programs, based on the performance of their alumni on the exam, according to their pass rate, average score, and their contribution to the total number of new CPA’s admitted to the profession. Candidates from public institutions perform better than candidates from private institutions. The research provides methodology that can be replicated in any profession that requires a professional license.